Single incision thenar muscle reconstruction using the free functional pronator quadratus flap - Aman, Martin; Böcker, Arne Hendrik; Thielen, Mirjam; Müller, Camillo; Bigdeli, Amir Khosrow; Kneser, Ulrich; Harhaus-Wähner, Leila (BMC surgery, 2021)
BackgroundInjuries to the thenar muscle mass or the thenar branch of the median nerve and resulting loss of thumb opposition lead to a massive impairment of hand function. For decades, reconstructive approaches were based on tendon transfers. To broaden the reconstructive repertoire, we present the free functional pronator quadratus flap as a viable alternative for functional reconstruction and provide a specification for its indication. We demonstrate our surgical technique to a single incision reconstruction using the free functional pronator quadratus flap. Based on a series of three patients, which were analyzed for hand function using Kapandji's score and the angle of Bourrel, grip strength and nerve conduction velocity in a two year follow up, we present an indication algorithm.ResultsAfter successful reinnervation of all flaps, we found an improvement of Kapandji's score from 4.30.94 preoperatively, to 8.7 +/- 0.47 after two years. Accordingly, the angle of Bourrel decreased from 75.75 +/- 3.45 degrees to 36.96 +/- 3.68 degree. Grip strength also improved from 14 +/- 2.2 kg to 26.2 +/- 1.2 kg. No impairment of wrist pronation was observed.ConclusionWe found excellent functional recovery of thumb opposition and strength, showing similar or even superior results compared to results from tendon transfers. With the benefit of a single incision surgery and therefore minimal donor site morbidity, this free functional muscle transfer is a viable alternative to classic tendon transfers.